2014
DOI: 10.1016/j.jpaa.2013.04.018
|View full text |Cite
|
Sign up to set email alerts
|

On words that are concise in residually finite groups

Abstract: Abstract. A group-word w is called concise if whenever the set of wvalues in a group G is finite it always follows that the verbal subgroup w(G) is finite. More generally, a word w is said to be concise in a class of groups X if whenever the set of w-values is finite for a group G ∈ X, it always follows that w(G) is finite. P. Hall asked whether every word is concise. Due to Ivanov the answer to this problem is known to be negative. Dan Segal asked whether every word is concise in the class of residually finit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Thus, we assume that G is virtually soluble. By Lemma 2.4 of [3] the derived series of G has only finitely many terms, that is, G (i) = G (i+1) for some positive integer i. It is sufficient to prove that G (i) is locally finite, because then factoring it out we get the case where G is soluble and the result is immediate from Lemma 8.…”
Section: Proofs Of the Main Resultsmentioning
confidence: 94%
“…Thus, we assume that G is virtually soluble. By Lemma 2.4 of [3] the derived series of G has only finitely many terms, that is, G (i) = G (i+1) for some positive integer i. It is sufficient to prove that G (i) is locally finite, because then factoring it out we get the case where G is soluble and the result is immediate from Lemma 8.…”
Section: Proofs Of the Main Resultsmentioning
confidence: 94%
“…Segal [12, p. 15] or A. Jaikin-Zapirain [6]). It was shown in [1] that if w is a multilinear commutator word and n is a prime-power, then the word w n is concise in the class of residually finite groups. We say that a word w is boundedly concise in a class of groups X if for every integer m there exists a number ν = ν(X, w, m) such that whenever |G w | ≤ m for a group G ∈ X it always follows that |w(G)| ≤ ν. Fernández-Alcober and Morigi [2] showed that every word which is concise in the class of all groups is actually boundedly concise.…”
mentioning
confidence: 99%
“…Moreover they showed that whenever w is a multilinear commutator word having at most m values in a group G, one has |w(G)| ≤ (m − 1) (m−1) . It was shown in [1] that if w = γ k is the kth lower central word and n a prime-power, then the word w n is boundedly concise in the class of residually finite groups. Recall that the word γ k is defined inductively by the formulae…”
mentioning
confidence: 99%
“…In recent years, several words were shown to be concise in residually finite groups while their conciseness in the class of all groups remains unknown. In particular, it was shown in [2] that if w is a multilinear commutator word and n is a primepower, then the word w n is concise in the class of residually finite groups. Further examples of words that are concise in residually finite groups were given in [13].…”
Section: Introductionmentioning
confidence: 99%